Compare the efficacy of chlosite gel as an adjunctive therapy after scaling and root planing - Neelu Verma; Charanjit Singh Saimbi; Sanjay Gupta; Avadhesh Kumar; Amitandra Kumar Tripathi (Contemporary Clinical Dentistry, 2022)
Aim: The present study was carried out to evaluate the clinical efficacy of scaling and root planing (SRP) alone and commercially available chlosite gel adjunctive to SRP in the treatment of chronic periodontitis. Materials and Methods: A total of 416 sites selected from 26 patients presenting with chronic periodontitis (age group ≥30 years) of both sexes, with pocket depth of ≥6 mm were recruited for the study. A split-mouth design was employed with one site receiving SRP alone (Group I) and the other receiving SRP followed by placement of commercially available chlosite gel (Group II) and all the clinical parameters-Plaque index (PI), Gingival index (GI), Probing Pocket depth and Clinical attachment loss (CAL) were recorded at baseline, 1 month, 3 months, and 6 months. Results: Results demonstrated that significant reduction in PI and GI scores were observed in both groups till the end of the study period (6 months). Probing depth and CAL also showed significant improvement in both the groups. However, Group II (sites which received SRP + Chlosite gel) showed greater improvements in all of these parameters compared to Group I (sites which received SRP only). Conclusion: The findings of this study suggest that the locally delivered commercially available chlosite gel along with mechanical debridement, resulted in a clinically meaningful improvement in all the clinical parameters.